2019
DOI: 10.1038/s41398-018-0331-3
|View full text |Cite|
|
Sign up to set email alerts
|

Brain region-specific alterations of RNA editing in PDE8A mRNA in suicide decedents

Abstract: Phosphodiesterases (PDE) are key modulators of signal transduction and are involved in inflammatory cell activation, memory and cognition. There is a two-fold decrease in the expression of phosphodiesterase 8A (PDE8A) in the temporal cortex of major depressive disorder (MDD) patients. Here, we studied PDE8A mRNA-editing profile in two architectonically distinct neocortical regions in a clinically well-characterized cohort of age- and sex-matched non-psychiatric drug-free controls and depressed suicide decedent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
(80 reference statements)
0
18
0
Order By: Relevance
“…GluA2 RNA editing may be a target for the development of drugs to ameliorate the long-term effects of stress on behavior. These data also indicate that reduced RNA editing is likely to contribute to the hippocampal deficits observed in psychiatric disorders associated with impaired SI, such as schizophrenia 8,39,40,105,106 , autism 19,38 , mood disorders 92,[107][108][109][110][111] and Alzheimer's disease 8,10,112,113 .…”
Section: Discussionmentioning
confidence: 74%
“…GluA2 RNA editing may be a target for the development of drugs to ameliorate the long-term effects of stress on behavior. These data also indicate that reduced RNA editing is likely to contribute to the hippocampal deficits observed in psychiatric disorders associated with impaired SI, such as schizophrenia 8,39,40,105,106 , autism 19,38 , mood disorders 92,[107][108][109][110][111] and Alzheimer's disease 8,10,112,113 .…”
Section: Discussionmentioning
confidence: 74%
“…Recently, there have been numerous studies on PDE8A and PDE8B, a family of cAMP specific PDEs (Fisher et al, 1998a;Hayashi et al, 1998;Soderling et al, 1998a;Glavas et al, 2001;Kobayashi et al, 2003;Dong et al, 2006Dong et al, , 2010Dong et al, , 2015Chen et al, 2009;Vang et al, 2010Vang et al, , 2016DeNinno et al, 2011;Tsai and Beavo, 2012;Brown et al, 2013;Demirbas et al, 2013;Maurice, 2013;Shimizu-Albergine et al, 2016;Basole et al, 2017;Johnstone et al, 2017;Kelly, 2018). PDE8A and B are expressed widely in human tissue (Wang et al, 2008) with functions identified in testosterone and corticosteroid production (Tsai et al, 2010;Demirbas et al, 2013), myocyte contraction (Patrucco et al, 2010), lymphocyte adhesion and chemotaxis (Dong et al, 2006(Dong et al, , 2015Vang et al, 2010Vang et al, , 2013Basole et al, 2017), memory and coordination , human airway smooth muscle regulation (Johnstone et al, 2017), strong association with immune protection against intracellular pathogens (Blanco et al, 2017), brain disorders associated with inflammation (Chimienti et al, 2019) and T cells in systemic lupus erythematosus (SLE) (Orlowski et al, 2008). In a recent study, single nucleotide polymorphisms in the PDE8 region were found to be associated with Sjögren's Syndrome (Taylor et al, 2017).…”
Section: Pde8a But Not Pde4 Is Controlling Activated T Cell Motilitymentioning
confidence: 99%
“…Specifically, a robust increase in editing on 5-HT2c-R was seen in the anterior cingulate cortex of suicide victims, linking the editing reaction in this cortical area to suicide risk [46]. Intriguing, phosphodiesterases (PDE), a key modulator of signal transduction downstream 5-HT2c-R, involved in inflammatory cell activation, memory and cognition, was differently edited between depressed suicide decedents and controls [47]. As already noted [48], Table 1 clearly indicates that literature data is not always consistent, which could be due to different factors such as the number of samples analyzed, inconsistency in the precise brain regions analyzed, the techniques used to measure editing levels, technical artefact associated to post-mortem brain etc.…”
Section: Rna Editing In the Serotonin Receptor 2cmentioning
confidence: 99%
“…Specifically, a robust increase in editing on 5-HT2c-R was seen in the anterior cingulate cortex of suicide victims, linking the editing reaction in this cortical area to suicide risk [ 46 ]. Intriguing, phosphodiesterases (PDE), a key modulator of signal transduction downstream 5-HT2c-R, involved in inflammatory cell activation, memory and cognition, was differently edited between depressed suicide decedents and controls [ 47 ].…”
Section: Adenosine To Inosine (A-to-i): the Most Common Form Of Rnmentioning
confidence: 99%